Penggunaan Emergency Stick Level (ESL) pada Mesin Bubut Tipe Basic Plus 100809 untuk Mempermudah Mahasiswa dalam Membubut di Laboratorium Produksi. - Yopi Yogasmara; Asep Ahmad Ruri Irwanto (UPT Laboratorium Terpadu, Universitas Diponegoro, 2021)
The limitations of the production laboratory in the form of providing tools can hinder turning activities. Based on the competency test scores in the basic machining practicum for the 2018/2019 academic year, it was found that there were still many UPI FPTK DPTM students who did not pass the competency test by 82% (23 people). This indicates that students still have difficulty turning. Student difficulties include the ability to produce work objects that do not exceed tolerance limits and the ability to take the time set in each turning work. The purpose of this study is to design a tool called Emergency Stick Level (ESL) which is used in the basic plus type 100809 lathe. The design of the Emergency stick level (ESL) includes the manufacture of butterfly nuts, stick level stoper), springs (springs), ESL housing (ESL body) and connecting nuts (extention nut). Aluminum was chosen as the basic material for making Emergency stick level (ESL) because it is easy to shape and corrosion resistant. The conclusion is that the presence of the Emergency stick level (ESL) makes it easier for UPI FPTK DPTM students to turn